Chinese shareholders' reaction to the disclosure of environmental violations: A CSR perspective - Huang Haifeng; Di Wu; Gaya J (International Journal of Corporate Social Responsibility (JCSR), 2017)
In the past decades, Corporate Social Responsibility (CSR) has attracted increasing attention, with Corporate Environmental Responsibility (CER or Environmental CSR) playing an ever important role. This paper aims to study whether and how Chinese shareholders are sensitive to the disclosure of environmental violations. Specifically, the issue is measured by the performance of the Chinese stock market. In order to answer this question, the authors conduct a two-dimensional 'environment-as-a-resource' framework, which assumes that the pressure on stock price after an environmental violation is from both externalities and internalities. The external pressure comes from environmental regulations, media attention, customer sensitivity and so on. The internal pressure is rooted in firm level actions, for example, previous pollution control and previous CSR performance. The paper starts by addressing theories of corporate social responsibility, corporate environmental management and market value management, followed by the advancement of foreign and domestic research. Then, based on the events in the Shanghai and Shenzhen stock exchanges from 2002 to 2014, the authors calculate the events' cumulative abnormal return. The explanatory factors in the regression model include external impacts of time trend and media attention; together with internal impacts of previous pollution situations and CSR performance. Complementing the notion of "environment-as-a-resource", the regression results reveal that, facing an environmental violation, Chinese shareholders react negatively. The negative reaction becomes weaker as time goes by, and is stronger in the years with heavier media environmental attention. Furthermore, some policy suggestions are proposed in light of the current CSR implementations by Chinese companies: 1) Strengthen the government's environmental scrutiny management to help the market punish environmental violators. 2) Encourage environmental accounting and environmental auditing for public companies. 3) Build up a broad environmental information platform comprising of interactions between the government, corporations and media. 4) Cultivate environmental awareness of company managers so it becomes worthy to invest in environment resources and gain better awareness of environmental responsibility.
Keywords: 650; Corporate social responsibility; Corporate environmental management; Shareholders' reaction; Environmental violation